Augmentation of intertransverse process lumbar fusion - Nawrocki, Michael A.; Martinez, Steven A.; Hughes, Joanne; Lincoln, James D.; Shih, Mei-Shu; Zheng, Hellen; Carroll, William J. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Spinal fusion surgery for alleviation of intractable lower back pain in humans is currently a primary therapeutic technique, with failure rates averaging between 5 to 35%. Implanted and external source-based electrical stimulation devices have been investigated in an attempt to increase osteogenesis at the fusion site in an attempt to reduce spinal fusion failure rates. The purpose of our study was to evaluate the efficacy of two co-processor systems and an additional system with an SIS generation field at 15.8 mA (rms) using biomechanical, dual-energy X-ray absorptiometry (DXA), and histomorphometric analyses, in rabbits following dorsolateral (= posteriolateral [in humans]) spinal fusion. Fifty-six male New Zealand White underwent bilateral lumbar spinal fusion by performing decortication of the transverse processes of lumbar vertebrae four and five with placement of autogenic cancellous bone graft harvested from the ilial wings. Four study groups were designated based on the type of IES device used for stimulation or as a control. Eight weeks after surgery all subjects were sacrificed and the quality and strength of the fusion masses were compared using radiographic, biomechanical, histomorphometry, and qualitative histological evaluation. While some variation existed within and between groups, Group 2 showed a significant improvement in all parameters measured as compared to the control group (P<0.05). The use of adjunct non-invasive surface IES for improving bony fusion rates for patients undergoing lumbar spinal fusion is supported by this study.
Keywords: Interferential stimulation; spinal fusion; posteriolumbar fusion; rabbit